A combined Dual Hot-Gas Bypass Defrosting method with accumulator heater for an air-to-air heat pump in cold region. (1st June 2015) - Kim, Jaehong; Choi, Hwan-Jong; Kim, Kyung Chun
Highlights: A novel defrosting cycle for heat pump operating in cold region is proposed. A combined defrosting cycle with DHBD and the accumulator heating method is developed. An induction heater (IH) is adopted as the accumulator heater. The combined DHBD–IH method sustained higher discharge temperature of the compressor. The combined method reduced 15% of the defrosting time than that of the RCD method. Abstract: The Dual Hot-Gas Bypass Defrosting (DHBD) cycle is an effective defrosting method compared to a Reverse Cycle Defrosting (RCD) method to remove frost from the outdoor heat exchanger (HEX) of an air-to-air heat pump, especially the outdoor temperature is above 0 °C. However, the DHBD method has a drawback when the heat pump operates in cold outdoor environment, below 0 °C due to rapid decrease in refrigerant temperature followed by lower hot-gas bypass temperature. In order to overcome lower discharge temperature of compressor, a combined defrosting cycle with DHBD and the accumulator heating method is developed. An induction heater (IH) is adopted as the accumulator heater. The dynamic performance and defrosting time are compared between the conventional RCD method and the combined DHBD–IH method using a medium size air-to-air heat pump of 16 kW under the condition of −5 °C outdoor temperature. Due to the additional heater, the combined DHBD–IH method sustained higher discharge temperature of the compressor and reduced 15% of the defrosting time than that of the RCD method with nonstop indoor heating operation. The overall heating capacity of the DHBD–IH cycle including defrosting mode was 2.5 kW higher than that of the RCD cycle.